2004
DOI: 10.1080/15287390490486761
|View full text |Cite
|
Sign up to set email alerts
|

Specific Non-Coplanar PCB-Mediated Modulation of Bottlenose Dolphin and Beluga Whale Phagocytosis Upon in Vitro Exposure

Abstract: Contaminant-induced immunosuppression by organochlorines (OC), particularly polychlorinated biphenyls (PCBs), has been suspected as a cofactor in the deaths of thousands of marine mammals. One important innate defense mechanism is phagocytosis, the ability of cells to ingest extracellular macromolecules. The present study was aimed at characterizing the immunomodulatory potential of representative OCs on phagocytosis in bottlenose dolphins and beluga whales. The ability of peripheral blood leukocytes to engulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Noncoplanar PCBs cause a variety of adverse effects, including increased release and decreased synthesis of insulin in rat insulinoma cells (Fischer et al 1996), changes in the concentrations and distribution of dopamine and 5-hydroxytryptamine in female rat brains (Chu et al 1996), increases in rat liver weight (Lecavalier et al 1997), reduced phagocytosis by neutrophils and monocytes in marine mammals (Levin et al 2004), and modulation of superoxide anion production in rat neutrophils (Brown and Ganey, 1995). PCBs also affect the regulation of a number of genes, the most studied being cytochromes P450 in liver (Chubb et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Noncoplanar PCBs cause a variety of adverse effects, including increased release and decreased synthesis of insulin in rat insulinoma cells (Fischer et al 1996), changes in the concentrations and distribution of dopamine and 5-hydroxytryptamine in female rat brains (Chu et al 1996), increases in rat liver weight (Lecavalier et al 1997), reduced phagocytosis by neutrophils and monocytes in marine mammals (Levin et al 2004), and modulation of superoxide anion production in rat neutrophils (Brown and Ganey, 1995). PCBs also affect the regulation of a number of genes, the most studied being cytochromes P450 in liver (Chubb et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…bottlenose dolphins (Tursiops truncatus), beluga whales (Delphinapterus leucas) and pinnipeds, while studied compounds are organohalogenated, i.e. PCBs (polychlorinated biphenyls), organochlorine and brominated compounds Levin et al 2004Levin et al , 2007Mori et al 2006). Nevertheless, there are also studies reporting immunotoxicity in relation to heavy metal exposure (e.g.…”
Section: In Vitro Researchmentioning
confidence: 99%
“…In addition, Levin et al (2004) have found that bottlenose dolphins are more sensitive to organochlorine mixtures than beluga whales thereby pointing towards a species-specific sensitivity. Various studies have also shown that organochlorine compounds can have an AhRindependent mechanism of action, thereby indicating that the sensitivity of marine mammals could not be predicted from results obtained from other species (Levin et al 2004(Levin et al , 2007Mori et al 2006). As bioassays are based on specific cell lines derived from other species like rodents or humans, one can argue that the observed responses to contaminant mixtures are not necessarily the same as the responses experienced by marine mammals in the wild.…”
Section: In Vitro Researchmentioning
confidence: 99%
See 2 more Smart Citations